'Jumping to conclusions' bias in functional movement disorders. Issue 4 (15th February 2012) - Pareés, Isabel; Kassavetis, Panagiotis; Saifee, Tabish A; Sadnicka, Anna; Bhatia, Kailash P; Fotopoulou, Aikaterini; Edwards, Mark J
Abstract : Background: Patients with functional neurological disorders often report adverse physical events close to the onset of functional symptoms. However, the mechanism via which a triggering event may set off a functional condition is lacking. One possibility is that patients make abnormal inferences about novel information provided by physical triggering events. In this study, the authors aimed to specifically investigate whether patients with functional movement disorders have abnormalities in probabilistic reasoning. Methods: The authors used a well-studied probabilistic reasoning paradigm, 'the bead task', in 18 patients with functional movement disorders and 18 healthy agematched controls. The authors assessed the number of beads that participants needed to reach a decision and changes in the certainty of their decisions when confronted with confirmatory or contradictory evidence. Findings: Patients with functional movement disorders requested on average significantly fewer beads before reaching a decision than controls (3 vs 6 beads). When confronted with potentially disconfirmatory evidence, patients showed a significantly greater reduction in confidence in their estimates than controls. 40% of patients reached a decision after one or two beads whereas no controls showed this bias. Interpretation: Patients with functional movement disorders requested less information to form a decision and were more likely to change their probability estimates in the direction suggested by the new evidence. These findings may have relevance to the manner with which patients with functional neurological disorders process novel sensory data occurring during physical triggering events commonly reported at onset of symptoms.